The Role of Authentic Local Resources and Social Capital in the Development of Sustainable Village Tourism - Sukaris Sukaris (Universitas Muhammadiyah Yogyakarta, 2024)
This study aims to determine the role of authentic local resources and social capital in influencing the development of sustainable village tourism. This research refers to the social exchange theory and the theory of resources base view, using 30 managers of the village tourism